A survey of patient satisfaction of patients attending a psychiatry outpatient clinic at a tertiary care centre - Jena, Shivananda; Gupta, Manushree (International Journal Of Community Medicine And Public Health, 2018)
Background: The concept of patient satisfaction in mental health services has eluded understanding in spite of large research body on this subject. Poor patient satisfaction leads to worse outcomes on psychiatric disorders. This study looked for social, demographic and clinical variables associated with patient satisfaction. Methods: 1100 eligible subjects were screened and then 519 alternate sample subjects were recruited for the survey based on the selection criteria. Social, demographic and clinical variables were assessed and PSQ-18 (Patient Satisfaction Questionnaire) was administered to all subjects. Results: 453 (87.28%) patients reported satisfaction and 66 (12.72%) of patients reported being unsatisfied with the service provided. Four sub-scales [“General satisfaction” (p<0.001), “Technical quality” (p<0.001), “Interpersonal manner” and “Communication” were found to be associated with patient satisfaction while other 3 sub-scales (“Financial aspects”, “Time spent with the doctor” and “Accessibility and convenience”) were not significantly associated with patient satisfaction. Conclusions: Both the technical and the interpersonal and communication skills of the doctor were important in determining patient satisfaction whereas the often believed variables like financial aspect and the time spent with the doctor did not affect patient satisfaction significantly.